2014
DOI: 10.1136/bmjopen-2014-004870
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of isolated gestational proteinuria progressing to pre-eclampsia: retrospective observational study

Abstract: ObjectivesSome women with isolated gestational proteinuria (IGP) later develop hypertension and are diagnosed with pre-eclampsia (PE). This study was performed to determine whether clinical features of such proteinuria preceding PE (P-PE) differ from those of other PE (O-PE).DesignRetrospective observational study after approval of the institutional review board of ethics.SettingA single university hospital. Proteinuria was defined as a protein-to-creatinine ratio (mg/mg; P/Cr) of ≥0.27 in the spot urine speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
5
25
0
1
Order By: Relevance
“…As FPR was consistently predictive of later PE in most studies6789101112131415161718192021222324, FPR has been accepted as a diagnostic aid for PE in conjunction with other clinical findings26. This was also confirmed in the present study; women with FPR >90 th percentile value had RR of PE = 4.98 (1.91–13.0) compared to women with FPR <90 th percentile value.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As FPR was consistently predictive of later PE in most studies6789101112131415161718192021222324, FPR has been accepted as a diagnostic aid for PE in conjunction with other clinical findings26. This was also confirmed in the present study; women with FPR >90 th percentile value had RR of PE = 4.98 (1.91–13.0) compared to women with FPR <90 th percentile value.…”
Section: Discussionsupporting
confidence: 85%
“…Some patients with PE first develop significant proteinuria in pregnancy (SPIP) defined as urine protein:creatinine ratio (PCR, mg/mg) >0.27 and subsequently hypertension1213. Isolated gestational proteinuria defined as SPIP in the absence of hypertension is a strong risk factor for PE13 and a 2 nd trimester cut-off level of PCR < 0.27 can differentiate between women with higher and lower risks of later developing PE6.…”
mentioning
confidence: 99%
“…Previous studies [9,22,23] have reported that patients with gestational proteinuria are more likely to develop PE in relation to non-proteinuric pregnant women, which is consistent with the findings of our study. However, proteinuria has been questioned as being an indicator of PE morbidity according to the different studies that have shown similar perinatal outcomes in severe PE group compared to pregnant women with severe gestational hypertension [20] .…”
Section: Characterization Of Atypical Preeclampsiasupporting
confidence: 83%
“…However, to our knowledge, there have been no reports regarding an association between nephrinuria (urine nephrin concentration) and podocyturia (density of urine podocytes) in patients with podocytopathies, including diseases other than PE. As PE women exhibit a gradual increase in proteinuria, 22,23 investigation of a longitudinal series of urine samples from PE women enabled analysis of this issue in this study. The degree of nephrinuria reflected the degree of podocyturia monitored by urine sediment Pod-mRNA and Nep-mRNA expression levels in this study in PE women.…”
Section: Discussionmentioning
confidence: 99%